Multi Level Education Katoga Improve The Competence of Health Cadres, Public Figure, and Family in Preventing, Early Detection and Handling Pregnancy Emergency - Ratna Hidayati; Dwi Setyorini (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Extraordinary policies have been launched by the government to reduce Maternal Mortality Rate/ Infant Mortality Rate (MMR/IMR) , however this has not been comparable with the expected results. The purpose of this study was to determine the effectiveness of Katoga's multi-level education on the competence of cadres, public figure, and families in preventing, detecting early and handling emergency pregnancy to reduce MMR/IMR. Methods: This research study used action research with stratified respondents, 10 health cadres who will provide training to 30 community leader respondents and subsequently public figure will provide training to 60 selected families with simple random sampling. The independent variable was multi-level education and the dependent variable was competence in early detection of emergencies in pregnancy. Data were collected using a questionnaire and analyzed by t-test. Results: The results showed that the increasing of the competence in preventing, early detecting and handling emergency pregnancy after receiving multilevel education training in health cadres from the previous value of 70 to 93; in community leaders from 61.1 to 80.5 and in families from 58.0 to 78.9. There was a significant increase in competency with multi-level education training in increasing competency in a larger population with a cadre pValue of 0.003; community leaders 0,000 and families 0,000. Conclusions: Community empowerment in the health sector through multi-level education can spread knowledge in preventing, detecting high-risk pregnancies early and managing maternal emergencies so as to facilitate the task of health nurses to obtain information about pregnant women detected as high-risk populations.